Estimating markups under nonlinear pricing competition - Eugenio J. Miravete; Lars-Hendrik Röller (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This paper provides a structural interpretation to the estimates of the shape and position of nonlinear tariffs. We focus on the evaluation of price-cost margins, and thus we need to identify marginal cost from an equilibrium model of nonlinear pricing competition. We estimate these price-cost margins using quarterly data from the early U.S. cellular telephone industry between 1984 and 1988. Our results indicate that the margins are increased under duopoly, due to a significant reduction in marginal costs. Moreover, we find that the price-cost margins vary over the consumption levels and that low end users are subject to higher price-cost margins than high-end users. The impact of competition further increases the margins in the low-end user segment, relative to high endusers. In that sense the benefits of competition, which are largely due to increased efficiencies, are passed on relatively more to high-end users. We also show that these findings are robust even if one includes a number of observable market demand and cost variables. – – Dieses Papier bietet eine strukturelle Interpretation der Schätzungen der Form und Position nichtlinearer Tarife. Dabei konzentrieren wir uns auf die Bewertung von Preisaufschlägen und müssen daher zunächst die Grenzkosten in einem Gleichgewichtsmodell nicht-linearen Preiswettbewerbs identifizieren. Wir schätzen diese Preisaufschläge, indem wir Quartalsdaten der jungen Mobilfunkindustrie der U.S.A. zwischen 1984 und 1988 verwenden. Die Ergebnisse deuten darauf hin, dass die Aufschläge in einem Duopol aufgrund signifikanter Grenzkostenreduktion größer sind. Außerdem lässt sich feststellen, dass die Preisaufschläge über die Konsumniveaus variieren und dass Nutzer im Niedrigsegment (,low-end') höhere Preisaufschläge zu tragen haben als ,highend'- Nutzer. Der Einfluß des Wettbewerbs vergrößert noch die Preisaufschläge im ,low-end'-Bereich im Vergleich zum ,high-end'. In diesem Sinne profitieren die ,high-end'-Nutzer mehr vom Wettbewerb, der sich vor allem in gesteigerten Effizienzen positiv niederschlägt. Diese Ergebnisse sind robust, wie gezeigt werden kann, sogar wenn eine Reihe beobachtbarer Marktnachfrage- und Kostenvariablen hinzugefügt wird.
Keywords: D43; D82; L96; 330; Estimation of Equilibrium Oligopoly Models; Competitive Nonlinear Pricing; Common Agency